Scheduling Time Slots for Class Conduction Using Genetic Algorithm - Vijayan, Vinodh P; Joseph, Neena; George, Neema; Mary Kurian, Simy (International Journal of Computer Sciences and Engineering, 2025)
Scheduling the class intervals using traditional methods like using on line spreadsheets is complicated and time consuming. The complexity will increase with more than one concern, pupil and teachers because the requirements become extra complex. It is tough to manage topics with multiple instructors or forming student businesses and assigning instructors. In addition, priority of topics or instructors, class hours are not taken into consideration for scheduling. Class scheduling using genetic algorithm, has been advanced to time table class rooms thinking about various resources and parameters. The proposed algorithm accepts diverse parameters like priority values for teachers and topics or elegance hours and give the satisfactory solution. Our new device makes the school room scheduling less difficult and also reduce the time required for scheduling.